FOUL PLAY: Exploring fouling behavior as an indicator of success in European Elite Football Leagues - Phatak, A.; Rein, R.; Memmert, D. (spinfortec2020digital: 13. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 24.-25. September 2020 in Bayreuth, 2020)
Fouling in football has been studied from the standpoint of ethics. The present study investigates fouling as an indicator of performance. Normalized fouling (Fouls and cards) from top European leagues were compared to end of season performance. The results suggested that fouling out of possession seems to be positively corelated to success across leagues but is the most effective in the English premier league.